ENERGY DIPLOMACY OF TURKEY - V. Ozdemir; I. A. Guliyev (Vestnik MGIMO-Universiteta, 2016)
The article deals with current issues of energy diplomacy of Turkey. The authors describe the main positive and negative results of Turkey's foreign energy policy in terms of the implementation of major energy projects. Geopolitical processes in the world, the conflict of interests of various countries in the political arena are important factors that affect the crude oil and natural gas pipeline projects. Particular attention is paid to the problems and prospects of cooperation between the Turkish Republic and the Russian Federation in the fuel and energy complex. The authors describe the interaction betweeen Russia and Turkey in the energy sector, including geo-economic interests of the countries in the Russian-Turkish gas dialogue. Turkey made efforts to position as an alternative gas supply route, taking advantage of concern about increasing Europe's dependence on Russian exports. Last years Turkey has set itself the important task - to turn from transit country into a regional gas hub. Ukrainian crisis increased the geostrategic importance of the Black Sea region to Russia, as well as strengthened the ambition of the Turkish side. The authors also highlight the prospects of the natural gas pipeline project from Russia via the Black Sea to Turkey and to the Turkish-Greek border, which named "Turkish stream". This project was frozen in terms of military and political processes at the end of 2015 in Syria.